2007
DOI: 10.1371/journal.pbio.0050144
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of CsoS1A and the Protein Shell of the Halothiobacillus neapolitanus Carboxysome

Abstract: The carboxysome is a bacterial organelle that functions to enhance the efficiency of CO2 fixation by encapsulating the enzymes ribulose bisphosphate carboxylase/oxygenase (RuBisCO) and carbonic anhydrase. The outer shell of the carboxysome is reminiscent of a viral capsid, being constructed from many copies of a few small proteins. Here we describe the structure of the shell protein CsoS1A from the chemoautotrophic bacterium Halothiobacillus neapolitanus. The CsoS1A protein forms hexameric units that pack tigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
238
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 156 publications
(255 citation statements)
references
References 54 publications
(70 reference statements)
16
238
1
Order By: Relevance
“…1,20 In the a-carboxysome from the chemoautotrophic bacterium Halothiobacillus neapolitanus [ Fig. 1(C)], which has been studied extensively, 1,7,21 the csoS1 genes code for three paralogs of this shell protein (CsoS1ABC). Similarly, the shell proteins in the b-carboxysome are encoded by a series of homologous ccm-type genes.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…1,20 In the a-carboxysome from the chemoautotrophic bacterium Halothiobacillus neapolitanus [ Fig. 1(C)], which has been studied extensively, 1,7,21 the csoS1 genes code for three paralogs of this shell protein (CsoS1ABC). Similarly, the shell proteins in the b-carboxysome are encoded by a series of homologous ccm-type genes.…”
Section: Introductionmentioning
confidence: 99%
“…Recent cryo-electron tomography studies provided important insights into the architecture of carboxysomes by showing that this bacterial microcompartment has a nearly icosahedral shape. 23,24 In complementary work, X-ray crystallographic studies have revealed the atomic structures of homologous BMC-type shell proteins from both types of carboxysome, including CcmK2 and CcmK4 from the b-carboxysome 6,7 and CsoS1A from the a-carboxysome. 7 The various carboxysome shell BMC proteins all form hexamers having a narrow central pore bearing a positive electrostatic potential.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations